الحدود تدرأ بالشبهاتوتطبيقاتها في القتل في الدفاع عن المعتديقدمت ىذه الرسالة استكمالا ب٤تطلبات نيل درجة اب٤اجستبّ في الشريعة الإسلبميةCancelled the punishment because of syubuhat andapplied for person who killed caused protected self - Surono, Yudi, Dr. M. Mu'inudinillah Basri, M. A, Dr. M. Abdul Kholiq Hasan, M.A., M.Ed (2014)
Amounts of the crime at the recent in Indonesia especially embelishment caused protected self. And this problem was causing difference between ulama in construing this problem. So this problem caused me interested to research it. From this thesis we could know that the rule (cancelled the punishment because of syubuhat), applied at the person who perforce has to kill because protected self, and influence of syuhubat in the giving punishment. This thesis is Isthinbathi(analysis), cause this research contains of the theories and collected directly the materials from the source of Islamic law, then how take the contents from the law of a theory based on rule and applied in their case who killed because protect self. And among of the result that obtained from this thesis is that the rule (cancelled the punishment because of syubuhat), very properly if applied at the current and that in truth (Syubuhat) have effect on punishment totality or could with low punishment and could be replaced with other punishment.